P142 Aeroallergen exposure alone is not responsible for sensitisation of workers to laboratory animal allergens. (December 2018) - Feary, J; Potts, J; Schofield, S; Canizales, J; Jones, M; Cullinan, P
Abstract : Background: Around 16 000 people in the UK work with laboratory animals with 75% of procedures being carried out on mice. Historical data, based largely on work with rats, suggest 15% develop IgE sensitisation to laboratory animal proteins and 10% clinical symptoms of laboratory animal allergy (LAA). The main risk factor for LAA is exposure to respirable aeroallergens. In recent years, conventional open cages have been replaced by individually ventilated cages (IVC) and while lower ambient aeroallergen levels are reported, the impact on LAA incidence is unknown. Methods: We surveyed laboratory animal workers at seven UK research institutions. Participants completed a questionnaire about work practices, underwent skin prick testing (to common aeroallergens and mouse epithelium) and had bloods taken for measurement of specific IgE to mouse epithelium and urine. We compared airborne Mus m 1 (the major mouse allergen) levels and the prevalence of sensitisation to mouse proteins in IVC-only and open cage units. Results: 750 individuals were recruited (response rate 85%); primary analyses were performed on data from 216 participants with <3 years' exposure to mice. Prevalence of sensitisation to mice was lower in IVC units compared with conventional cage units (2.4% (n=2) vs 9.8% (n=13); p=0.052). In IVCs the prevalence of sensitisation varied from 0% to 9.5%. Aeroallergen levels were generally lower in the IVC units. Mask usage for tasks associated with high allergen exposure (handling mice or soiled bedding) and mask 'fit' testing was more common in IVC units where prevalence of sensitisation was low or zero. Prevalence of atopy to common aeroallergens did not vary significantly between units (figure 1). Conclusions: In contemporary practice, the prevalence of sensitisation to mouse proteins is generally low and significantly so in those who have worked only in IVC units. The variation in sensitisation in IVC units was not fully explained by lower aeroallergen levels but also appears related to use of respiratory protective equipment, perhaps a proxy for a proactive approach to occupational health and safety. Our results suggest that LAA is now largely preventable using a combined approach of allergen control measures with IVCs and adherence to 'good practice'.